Pineapple residue ash, clinoptilolite zeolite and air-dried peat as tropical peat soil amendments and greenhouse gas emissions for pineapple cultivation - Liza Nuriati Lim Kim Choo,
Pineapple cultivation on nutrient deficient acidic peat soils causes poor growth, yield and fruit quality of pineapples. Fertilization activities and burning pineapple residues on peat soils releases carbon dioxide (CO2), nitrous oxide (N2O), and methane (CH4) into the atmosphere. There is a need to improve nutrient holding capacity of peat soils and mitigate greenhouse gases in pineapple cultivation because 90% of pineapples are planted on peat soils in Malaysia. The general objective of this study was to determine the potential of pineapple residue ash (PA), clinoptilolite zeolite (CZ), and air-dried peat (ADP) as soil amendments for pineapple cultivation. The specific objectives were to determine (i) physicochemical properties of a drained sapric peat soil, (ii) physicochemical and morphological properties of PA, CZ, and ADP, (iii) effects of PA, CZ, and ADP in controlling ammonium, nitrate, phosphorus (P), and potassium (K) loss from peat soils, (iv) effects of PA, CZ, and ADP in improving soil N, P, and K availability, uptake and use efficiency, growth performance, fresh fruit yield, and quality of pineapple fruits, and (v) effects of PA, CZ, and ADP on CO2, N2O, and CH4 emissions from peat soils cultivated with pineapples. Laboratory leaching experiments utilizing the Completely Randomized Experimental Design (CRD) were conducted to determine the effectiveness of PA, CZ, and ADP in controlling ammonium, nitrate, P, and K loss from peat soils, whereas field experiments in Randomized Complete Block Design and ion exchange resin methods were used to determine macronutrients availability in pineapple cultivation. The effects of PA, CZ, and ADP fertilization on CO2, 2O, and CH4 emissions from peat soils were determined using the closed chamber and laboratory incubation methods. Treatments evaluated in this study were (i) different amounts of PA, CZ, and ADP (25, 50, and 100% of the recommended pineapple fertilizer rate) + NPK fertilizer, (ii) co-application of PA, CZ, and ADP (10, 20, 25, 50 and 70% of the recommended pineapple fertilizer rate) + NPK fertilizer, (iii) NPK fertilizer, and (iv) peat soil alone. The peat soils with PA, CZ, and ADP increased ammonium, nitrate, P, and K availability because of the adsorption of these macronutrients onto their charged surfaces via ion exchange, surface complexation, hydrogen bonding, electrostatic attraction and repulsion, and physisorption mechanisms. Ammonium, nitrate, P, and K availability ii varied with soil depth because of the high preferential flow of the peat soil water. Coapplication of CZ (25%: 5 g) and NPK fertilizers (20 g) was more effective in increasing N availability, N uptake and use efficiency, fresh fruit weight, yield, and fruit sweetness (13.32 °Brix) of pineapples because CZ could synchronize the availability of N ions for pineapple uptake. Amending NPK fertilizers with PA (25%: 5 g) was more effective in increasing P availability, uptake and use efficiency, whereas combined use of ash (20%: 4 g), zeolite (10%: 2 g), and air-dried peat (70%: 14 g) was more effective for K. The use of PA (25%: 5 g) decreased CO2 and N2O emissions by 33.9% and 23.4%, respectively due to the adsorption of anionic organic compounds, ammonium, nitrate, CO2, and N2O onto the charged surface of ash via hydrogen bonding, electrostatic repulsion, and physisorption. Soil CO2, N2O, and CH4 emissions were regulated by moderate soil temperature variation throughout the pineapple growth period. Ability of PA and CZ to buffer the peat soil pH reduced the need for liming. Monthly fertilization using compound NPK fertilizers (20 g) in conjunction with CZ (25%: 5 g) and PA (25%: 5 g) is promising and could be adopted by local farmers to improve soil and pineapple productivity in addition to minimizing greenhouse gases in drained peat soils.